Yönetim Felsefesi Bağlamında Doğu ve Batı İttihad Eder mi? Gazali ve Machiavelli Üzerinden Hermenötik Bir Değerlendirme - Tuğba ÇİÇEK; Yunus Emre TAŞGİT; Zülkif DAĞLI (Gazi Akademik Bakış)
In this study, it is aimed to compare the views of Ghazali and Machiavell including their experiences on successful management, and to examine the situation / possibility of the Eastern and Western view points in the context of management philosophy. Gazali and Machiavell are people who live in different cultural conditions and present philosophically original perspectives to the field of management with their theoretical and practical inference, advice and experience in these periods. This reflections are relatively continuing today. In this direction, the Works called “Nasihatü'l-Muluk” addressed by Ghazali representing the East, and “Prens” written by Machiavell representing the West, were evaluated with an approach that takes in to account the basic principles of the qualitative research method. In addition to identifying the original aspects, common views and different points of view of thinkers about management, the features of the unification of both philosophies have been the subject of discussion. According to the results of the book reviews, Ghazali's managerial thoughts were collected in 17 categories and Machiavell's manageria lthoughts were collected in 14 categories. Both philosophies have close perspectives on issues such as the characteristics that a manager should have, communication management, commanding and obedience, referring to the opinions of others, and qualifications required in assistants. However, it has been determined that these philosophies differ significantly on the conceptual and emotional level in terms of their point of view, especially in specific issues such as generosity, punishment, resorting to violence and hostility.